Ecological Role of Siombak Lake as a Nursery and Feeding Ground for Aquatic Species in the Belawan Estuary, Indonesia - Ahmad Muhtadi; Ahyar Pulungan; Rizal Mukra (BRIN Publishing, 2025)
Tidal lake is a coastal lake whose water condition is influenced by the dynamics of tides. This lake serves as a habitat for a diverse array of aquatic biota, including freshwater, brackish, and marine species. This study aims to describe the distribution of larvae, juveniles, crustacea, and adult fish in the context of the coastal lake's role as a nursery and feeding ground. The study was conducted from September 2018 to August 2019, at Lake Siombak, a coastal lake located in the Belawan River estuary along the northern coast of Medan City, Indonesia. Data were collected at high and low tides during the full moon. Larva and juvenile fish? sampling used larval nets with a mesh size of 300 μm and a diameter of 60 cm, while adult fish were caught with gill nets with a mesh size of 1 inch and a dimension of 10 × 2 m. Crustaceans were captured with traps. The research found nine families consisting of six fish families, two crustacean family, and one cnidarian family. The abundance of larvae and juveniles found was 17 to 1797 individuals per 100 m-3. At the high tides, the composition of Ulmaridae (jellyfish: Aurelia aurita) that was caught reached 57.7%. While at low tides, there were more Penaeid families in the Mysis phase, reaching 78.6%. The abundance of Mysis (Penaeid) and jellyfish indicates that the lake serves as a nursery ground for post larvae crustaceans and jellyfish. The presence of adult fish migrating from the sea and Belawan River indicates that the lake functions as a feeding ground in the Belawan estuary. Therefore, Lake Siombak still plays a crucial role as a nursery and feeding ground for fish, crustaceans, and jellyfish originating from the Belawan River estuary and its surrounding areas. Preserving the sustainability of this lake is crucial to ensuring the continued productivity of fisheries in the Belawan River estuary.